PENYULUHAN PANGAN BERPOTENSI GIZI UNTUK PENCEGAHAN STUNTING DI DUSUN TELAGA PANGE DESA RUMAHTIGA KOTA AMBON - Heni Mutmainnah; Nana Ronawan Rambe; Corneli Pary; Laila Sahubauwa; Janaba Renngiwur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2023)
Stunting is a condition of chronic malnutrition in children which can have an impact on children's motor and verbal development as well as affect their cognitive development and productivity in adulthood. The prevalence of stunting in Indonesia in 2021 is 24.4% and in Maluku the stunting rate is 28.70%. This figure is higher than the WHO threshold, which is 20%. The purpose of carrying out this PKM activity is to provide education regarding the dangers of stunting in children and efforts to prevent stunting through training in making nutritious food innovations for stunting prevention so that it can be a solution for people in the regions in improving their standard of living. The method used in this activity is lectures with slide media and the practice of making nutritious food for toddlers. The results of the socialization show that the community understands the dangers of stunting on the growth and development of children and the community is able to innovate nutritious foods for toddlers.